Native C++ software in engineering as a high-performance alternative to managed software - Cruz-Simões-de-Almeida, Francisco Miguel (2014)
In this article, we will make a case for the resurgence and importance of the C++ native language and an overview of how it has recently evolved into a modern language. We hope that this provides context to why many more developers are considering using this multi-paradigm programming language in detriment of other, often classified as productive, managed programming languages. We refer to native languages as those where a compiler generates native executable machine code, and managed languages as those where a compiler generates byte compiled instructions, intended to be interpreted and executed by a virtual machine, which is in that case a requirement to execute byte compiled code. Java is an example of such a language. This article assumes that the reader has a basic knowledge of, or familiarity with Algol based languages, including C, C++, Java and C#.